1990
DOI: 10.1007/bf00228889
|View full text |Cite
|
Sign up to set email alerts
|

Neural control of vocalization in bats: mapping of brainstem areas with electrical microstimulation eliciting species-specific echolocation calls in the rufous horseshoe bat

Abstract: Summary. 1. The functional role of brainstem structures in the emission of echolocation calls was investigated in the rufous horseshoe bat, Rhinolophus rouxi, with electrical low-current microstimulation procedures. 2. Vocalizations without temporal and/or spectral distortions could be consistently elicited at low threshold currents (typically below 10 gA) within three clearly circumscribed brainstem areas, namely, the deep layers and ventral parts of the intermediate layers of the superior colliculus (SC), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 30 publications
2
54
0
Order By: Relevance
“…The breathing rates obtained with these methods mirrored rates obtained using the whole-body plethysmograph, and echoed results obtained with other more invasive techniques (Schuller and Rübsamen, 1981;Rübsamen and Betz, 1986;Hartley and Suthers, 1988;Suthers, 1988;Suthers et al, 1988;Schuller and Radtke-Schuller, 1990). Furthermore, the vocal temporal patterns recorded under these conditions compared favorably to earlier field and behavioral reports for naturally behaving unrestrained horseshoe bats (Schnitzler, 1968;Neuweiler et al, 1987;Tian and Schnitzler, 1997;Smotherman and Metzner, 2005), which indicates that the vocal and respiratory musculature was performing naturally during these electrophysiological studies.…”
Section: Methodssupporting
confidence: 76%
“…The breathing rates obtained with these methods mirrored rates obtained using the whole-body plethysmograph, and echoed results obtained with other more invasive techniques (Schuller and Rübsamen, 1981;Rübsamen and Betz, 1986;Hartley and Suthers, 1988;Suthers, 1988;Suthers et al, 1988;Schuller and Radtke-Schuller, 1990). Furthermore, the vocal temporal patterns recorded under these conditions compared favorably to earlier field and behavioral reports for naturally behaving unrestrained horseshoe bats (Schnitzler, 1968;Neuweiler et al, 1987;Tian and Schnitzler, 1997;Smotherman and Metzner, 2005), which indicates that the vocal and respiratory musculature was performing naturally during these electrophysiological studies.…”
Section: Methodssupporting
confidence: 76%
“…Given the operating range suggested by the distribution of BDs in the SC, 3D neurons may function particularly during the approach sequence of insect pursuit when the bat is between 1 and 2 m from the target (Kick and Simmons, 1984). In support of a role for the SC in approach-tracking behavior, we have shown that microstimulation elicits movements of the head and pinnae coupled to the production of sonar vocalizations (Valentine and Moss, 1997) (see also Schuller and Radtke-Schuller, 1990). The directional control of vocal behavior along an axis of closing distance is an integral part of the bat's acoustic orientation, and our single-unit and microstimulation data fit the general notion that the SC is involved in coordinating species-specific orienting behaviors.…”
Section: Behavioral Relevancementioning
confidence: 75%
“…This network potentially includes several midbrain structures, such as the superior colliculus, the periaqueductal gray, and areas laterally and ventrally adjacent to the periaqueductal gray (Suga et al, 1973;Jürgens and Pratt, 1979;Larson and Kistler, 1986;Rübsamen and Betz, 1986;Thoms and Jürgens, 1987;Schuller and Radtke-Schuller, 1990;Kirzinger and Jürgens, 1991;Larson, 1991;Jürgens and Lu, 1993;Gerrits and Holstege, 1996;Schuller et al, 1997;Jürgens, 1998Jürgens, , 2000Jürgens, , 2002Behrend and Schuller, 2000). This midbrain network can function independently from higher-order structures of vocalization control, such as the cingulate cortex (Movchan and Burikova, 1982;Movchan, 1984;Gaioni et al, 1990;Riquimaroux et al, 1992), and lesions at the level of the midbrain dramatically affect sound production in various mammals (Movchan, 1980;Movchan and Burikova, 1982;Kirzinger and Jürgens, 1985;Schuller, 1986;Konstantinov et al, 1988;Jürgens, 1998Jürgens, , 2002.…”
Section: Discussionmentioning
confidence: 99%
“…DSC can even be elicited in stationary horseshoe bats by presenting echo mimics, i.e., electronically delayed and frequency-shifted playbacks of the bat's own calls (Schuller et al, 1974). The present study was designed to test the role of specific regions in the brainstem tegmentum suspected to be involved in the control of call frequencies (Movchan, 1980;Jürgens, 1985, 1991;Metzner, 1989Metzner, , 1993Metzner, , 1996; Schuller and Radtke- Schuller, 1990; Holstege et al, 1997;Schuller et al, 1997;Pillat and Schuller, 1998). We focused on the area ventral to the inferior colliculus and medial to the nuclei of the lateral lemniscus, which included the paralemniscal tegmentum at its anterior end and the parabrachial nuclei (PB) at its posterior end.…”
Section: Introductionmentioning
confidence: 99%